INFLUENCE OF EXPORT AND IMPORT TOWARD ECONOMIC GROWTH IN CANADA IN 2010-2019 - Andi Triyawan; Hafizah Latifa; Lukmon Lanre Seriki; Ahmed Alfaqeeh (STIE Pelita Nusantara Semarang, 2021)
Economic growth greatly affects the stability of a country's economy. Because it is very important for a country to make efforts to maintain the stability of economic growth or even increase it. Economic growth is influenced by various factors, including international trade. As a developed country, Canada does a lot of export activities. However, there were not a few imports. This study aims to analyze how the influence of exports and imports on GPD in Canada. This research uses secondary data from 2010-2019 which is obtained from Worldbank. This study uses multiple linear regression analysis. The results showed that the level of import value and export value in Canada in 2010-2019 has no significant effect on economic growth in terms of the level of GDP value. Both collectively and partially, the value of exports and the value of imports have no effect on the value of GDP in Canada in 2010-2019.